Volume 1: 23rd Computers and Information in Engineering Conference, Parts a and B 2003
DOI: 10.1115/detc2003/cie-48194
|View full text |Cite
|
Sign up to set email alerts
|

Reeb Graph Based Shape Retrieval for CAD

Abstract: Our recent work has described a framework for matching solid of mechanical artifacts models based on scale-space feature decomposition. In this work we adopt a method of comparing solid models based on Multiresolutional Reeb Graphs (MRG) similarity computations. This method was originally proposed by Hilaga et al. in [1]. Reeb Graph technique applies MRG structure to comparisons of approximate models found in the graphics community, such as polygonal meshes, faceted representation and Virtual Reality Modeling … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(26 citation statements)
references
References 17 publications
0
26
0
Order By: Relevance
“…Application-independent feature based approaches based on skeletons [Iyer04,Lou04,Sund03], shock graphs [Siddi99], Reeb graphs [Besp03,Hila01] and slope diagram [Ghos96,Tuzi00] have been also developed. However, these approaches tend to filter out important geometric details that play an important role in assessing similarity between machined parts.…”
Section: Introductionmentioning
confidence: 99%
“…Application-independent feature based approaches based on skeletons [Iyer04,Lou04,Sund03], shock graphs [Siddi99], Reeb graphs [Besp03,Hila01] and slope diagram [Ghos96,Tuzi00] have been also developed. However, these approaches tend to filter out important geometric details that play an important role in assessing similarity between machined parts.…”
Section: Introductionmentioning
confidence: 99%
“…Their method uses Reeb graphs based on a quotient function defined by an integral geodesic distance. Bespalov et al [12] investigate the application of Hilaga's method to solid models. They found that for solid models, minor changes in topology may result in significant differences in similarity.…”
Section: Reeb Graph Based Similaritymentioning
confidence: 99%
“…Hilaga et al (2001) used integral geodesic distance as a quotient function. Bespalov et al (2003) implemented Hilaga's procedure on solid models. They concluded that reeb graph matching method was sensitive to topology of 3D models and more work should be done to inhance the method.…”
Section: Related Workmentioning
confidence: 99%